METODE KUMAR UNTUK MENYELESAIKAN PROGRAM LINIER FUZZY PENUH PADA MASALAH TRANSPORTASI FUZZY - S., Mohammad Ervan; Irawanto, Bambang (MATEMATIKA, 2016)
In this paper, we discusses fully fuzzy linear programming in transportation problem. To find the fuzzy optimal solution of the problem with equality constraints, we use Kumar’s Method. The value of the fuzzy optimal solution obtained is used to find the optimal value of fuzzy objective function. Then do defuzzification to obtain crisp optimal solutions by using Ranking Function. To illustrate the Kumar’s Method, we give a example as iteration